Синергія держави та бізнесу для забезпечення промислової безпеки - Матюхін, О. Б. (ХНУРЕ, 2023)
The report highlights the importance of ensuring environmental safety at industrial facilities. It explains that this requires identifying risks and taking measures to reduce them, as well as complying with environmental regulations and standards.
Keywords: industrial facilities; environmental safety